The Relationship Between Protein and Iron Intake Adequacy Levels and the Incidence of Anemia Among Female Adolescents at SMA N 6, Jambi City - N.S, Delta Eka Putri; Iswanto , Iswanto; Kasyani , Kasyani (Journal of Nursing, 2025)
The adolescent population (aged 10-19 years) in Indonesia constitutes 26.2% of the total population, with 49.1% being female. According to the 2017 Indonesian Demographic and Health Survey, the prevalence of anemia among children aged 5-12 years in Indonesia is 26%, while it is 23% among females aged 13-18 years. Similarly, the 2016 Household Health Survey (SKRT) reported that the prevalence of anemia among female adolescents aged 15-20 years is 57.1%. The overall prevalence of anemia among adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia.The objective of this study was to determine the relationship between the adequacy levels of protein and iron intake and the incidence of anemia among female adolescents at SMA N 6 Jambi City. This research employed a survey method with a cross-sectional study design. Data analysis was conducted using univariate and bivariate methods, involving 2x24-hour food recall and hemoglobin (Hb) measurement using an Easy Touch GCHb device. The results of this study showed a significant relationship between protein intake adequacy levels and anemia incidence (p-value = 0.000) and between iron intake adequacy levels and anemia incidence (p-value = 0.000).